MEMPERKUAT KARAKTER PESERTA DIDIK MELALUI IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS HOTS PADA PEMBELAJARAN PPKn - Umi Chotimah; Nyimas Aisyah; Meryansumayeka Meryansumayeka (Bhineka Tunggal Ika: Kajian Teori dan Praktik Pendidikan PKn, 2020)
Abstract: Pancasila and Civic Education (called PPKn) aims to develop the character values of students in which there is a component of knowledge, awareness or will, and actions to carry out these values. This study aims to determine the impact of the implementation of learning models based on High Order Thinking Skills (HOTS) in strengthening the character of students in learning PPKn in SMA Negeri 1 Tanjung Raja. This research uses descriptive research method with the sampling technique used is purposive sampling. The sample in this study is 30 students in grade X MIPA 3. Data were collected using observation techniques and documentation. Based on the results of data analysis and discussion, it can be concluded that the implementation of the HOTS-based learning model can strengthen the character of students. Keywords: character, HOTS Based-Learning Model, PPKn